Combined effect of a reduced dose of 1, 3-dichloropropene and dimethyl disulfide on soilborne pests and tomato growth. (July 2019) - Mao, Liangang; Jiang, Hongyun; Zhang, Lan; Zhang, Yanning; Sial, Muhammad Umair; Yu, Haitao; Cao, Aocheng
Abstract: The effects of 1, 3-dichloropropene (1, 3-D) plus dimethyl disulfide (DMDS) soil treatments on soilborne pests and tomato growth were evaluated in one laboratory study and two field trials. The laboratory study established that the combined effects were more efficient than the individual effects. The combinations completely suppressed the growth of Abutilon theophrasti and Digitaria sanguinalis and provided excellent control efficacy (>90%) against Meloidogyne spp., good effects (>86%) against Fusarium spp., and moderate activity (>61%) against Phytophthora spp. In the two field trials, compared to the untreated control, 1, 3-D:DMDS (1:4) (50 g/m 2 ), both at a 50% reduced dose, successfully controlled the damage of Meloidogyne spp. to tomato roots with evidence of a low root galling index (4.2% and 9.6%, respectively), sharply suppressed the pathogenic activity of Fusarium spp. and Phytophthora spp. shown with a low root disease index (both 8.3%) and significantly ( P  = 0.05) increased tomato yield and income, which was similar to the methyl bromide (MB) standard dose treatment (50 g/m 2 ) and DMDS standard dose treatment (80 g/m 2 ) but better than the 1, 3-D standard dose treatment (20 g/m 2 ). The results suggest that 1, 3-D:DMDS (1:4) soil treatments (50 g/m 2 ) could be applied in tomato production to prevent soilborne pests. Highlights: 1, 3-dichloropropene (1, 3-D) + dimethyl disulfide (DMDS) at 1:4 was selected. 1, 3-D:DMDS (1:4) showed synergistic effects on various soilborne pests. Two tomato field trials evaluated the efficacy of 1, 3-D:DMDS (1:4) at 50 g/m 2 . 1, 3-D:DMDS (1:4) was recommended to replace methyl bromide in tomato in China.